Sistem Penjadwalan Pemupukan dan Pengapuran untuk Peternakan Udang Vanami Menggunakan Teknologi IoT dan Algoritma Fuzzy Logic - Mohammad Robihul Mufid; Arif Basofi; Yunia Ikawati; Saniyatul Mawaddah; Darmawan Aditama; Mochammad Jauhar Ulul Albab (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2022)
The most common type of ponds found in most areas of Lamongan is shrimp ponds (vanami). One of the problems is the disease that often affects shrimp farmers. The cause of this disease include rapid changes in pH, which will stress the shrimp and will affect the immunity of the shrimp itself. The solution to this rapid change in pH is to immediately add fertilizer or liming. In this study a system for monitoring PH will be created so that fertilization or liming can be carried out as early as possible. This system is built using a PH sensor and a fuzzy logic algorithm. This research also applies the MQTT protocol to send data from the PH monitoring system to end user devices. The test results show that the PH monitoring system that is made works as needed with an error rate of 0.018. Besides that, it also meets expectations when testing fuzzy logic on the system because the calculation results are the same between the manual and the system.